The impact of social capital on crime: evidence from the Netherlands - I. Semih Akçomak; Bas ter Weel (Institute for the Study of Labor (IZA), 2008)
This paper investigates the relation between social capital and crime. The analysis contributes to explaining why crime is so heterogeneous across space. By employing current and historical data for Dutch municipalities and by providing novel indicators to measure social capital, we find a link between social capital and crime. Our results suggest that higher levels of social capital are associated with lower crime rates and that municipalities' historical states in terms of population heterogeneity, religiosity and education affect current levels of social capital. Social capital indicators explain about 10 percent of the observed variance in crime. It is also shown why some social capital indicators are more useful than others in a robustness analysis.
urn:nbn:de:101:1-20080723145
Keywords: A13; 360; Social capital; crime; the Netherlands; Kriminalität; Social Capital; Gemeinde; Schätzung; Niederlande